BIOCHEMICAL CHANGES IN THE PROFILE OF CARBOHYDRATE, PROTEIN AND TRIGLYCERIDES IN THE BLOOD OF CLARIAS BATRACHUS DUE TOSUBLETHAL TREATMENT WITH INSECTICIDE ROGOR. - NANDANI SHARAN,; RITA GUPTA; RAKRITI VERMA (The Bioscan, 2015)
In present study, the toxicity of insecticide rogor on biochemical parameters (carbohydrate,protein and triglycerides) of fresh water fish Clariasbatrachus were estimated.The LC 50 ( 96 hours) of rogor for fish have been calculated as 4.5μl/L . Two sub lethal concentration selected in the experimental protocol were 1μl/L and 2.5μl/L of Rogor and accordingly stock solutions of rogor were prepared using distilled water.Fishes were sacrificed after 5 th ,10 th ,15 th days of exposure.The total protein count shows great variations ,at 1μl/L , the total protein first decreased on 5 th day by 39.7% but increased on 10 th and 15 th day although it was 15.8% lower than the protein count of controlled fish. However, on 2.5μl/L the serum protein of treated fish increased by 10.5% on 5 th day of the treatment and on 15 th it showed an increase of 39.5% as compared to the controlled fish. The glucose level also increased in comparison to the controlled fish. On 1μl/L , the serum glucose increased by 15% on 5 th day of the treatment but on 10 th and 15 th day it decreased by 3.9% and 15% respectively. Whereas on 2.5μl/L ,the serum glucose increased by 18% on 5 th day,33% on 10 th day and 29% on 15 th day of the treatment. Triglycerides shows reduction in both doses , at 1μl/ L triglyceride reduced by 1.7%, 16.7% and 19.5% respectively, on 5 th day ,10 th day and 15 th day . On 2.5μl/L the decline in the triglyceride of treated fishes in comparison to control fish, on 5 th , 10 th and 15 th day are 30.6%, 39.6% and 41.6% respectively. This shows that rogor exposure hampers the nutritional value of these commercially important fishes.